Adherence to the nutritional treatment and body composition: A cross-sectional study in patients with obesity or overweight [La adherencia al tratamiento nutricional y composición corporal: Un estudio transversal en pacientes con obesidad o sobrepeso] (2007)
To assess nutritional adherence to treatment among obese or overweight patients and to examine the relationship between anthropometrical variables, 94 subjects between 20-50 years old randomly selected were recruited at two nutritional health centers in Medellin-Colombia. Nutritional adherence to treatment was evaluated using a questionnaire, with a total score above 24 considered as adherent to the treatment. In addition, socio-demographic information was obtained and anthropometrical variables were measured. We used descriptive statistical, Kolmogorov-Smirnov test, Chi-square for proportions comparison, and Student T test or U Mann Whitney for means comparison. A 68% of the patients were classified as no adherent to the nutritional treatment, with significant differences found according to physical activity (p= 0,013). Mean weight (p= 0,014), BMI (p= 0,026), waist circumference (p= 0,005) and waisthip ratio (p= 0,022) differed according to adherence, being significantly higher in non adherent patients. Percent body fat did not change by degree of adherence. However when controls were separated by gender the results were significant for both men and women. Nutritional adherence to treatment in patients on a diet for weight reduction produces significant changes in body composition. © 2007 Sociedad Chilena de Nutrición, Bromatología y Toxicología.